Case Series on Imaging Features of Trilateral and Quadrilateral Retinoblastoma: What Radiologists Need to Know - Fiona, Fiona; Yuli Anandasari, Pande Putu; Margiani, Ni Nyoman (Faculty of Medicine Universitas Padjadjaran, 2024)
Objective: To identify the differences between trilateral and quadrilateral retinoblastoma based on radiologic imaging.Case: We found three cases of retinoblastoma at Sanglah General Hospital. The retinoblastoma patients we found were boys under the age of 5. The first patient presented with swelling, pain, and impaired vision in the right eye. The second and third patients presented with eye protrusion and leukocoria. Computed tomography (CT) imaging revealed a calcified mass in the intraorbital region that extended to the cerebral hemispheres. It may be accompanied by hair-on-end periosteal reaction. In the first patient, the mass extended to the pineal gland. In the second and third patients, the mass extended to the suprasellar and pineal regions. Trilateral retinoblastoma consists of a primordial midline neuroectodermal tumor that originates in the pineal or suprasellar region. It is an uncommon combination of unilateral or bilateral retinoblastomas. Quadrilateral retinoblastoma, on the other hand, presents with bilateral retinoblastoma and tumors in both the suprasellar and pineal regions. The histopathology of trilateral and quadrilateral retinoblastoma shows a different pattern from retinoblastoma.Conclusion: Retinoblastoma poses one of the most challenging problems due to its distinct patterns of growth, extension, and recurrence. Intracranial metastasis of trilateral and quadrilateral retinoblastoma exhibits a different pattern. The prognosis and diagnosis of retinoblastoma are significantly influenced by clinical examination, radiologic imaging, and histopathology.